Women and the city: the urban experiences of women entrepreneurs, self-employed women and women-led business in Twist street and surrounds, Hillbrow, Johannesburg. - Soudien, Carla Thandi (My University, 2019)
This dissertation reviews the role of the urban environment in facilitating the economic empowerment of women, looking, particularly at women entrepreneurs. The study is framed conceptually using a feminist, post-colonial lens and acknowledges complexity in relation people’s experiences based on their gender, locality, citizenry, race and class. The literature review portion of the study considers scholars’ work in the fields of gender, urbanism and entrepreneurship. The study interrogates overlapping themes in relation to gendered social hierarchies in the realms of urbanism and entrepreneurship, reviewing both opportunities and constraints during all phases of the research. The empirical portion of the study comprises twenty interviews with women business owners in and around Twist Street in Hillbrow. The interviews included a mapping exercise in which the respondents depicted their daily movements graphically. In addition to the interviews, I carried out a mapping audit of the streetscape of three blocks of Twist Street, between Pretoria and Kapteijn streets. This mapping audit has assisted with understanding what the range of businesses are being run in this street, how many are run or owned by women and how many are run or owned by men. The fieldwork study sought to explore the respondents’ everyday experiences related to housing, transportation, support networks, domestic care work, agglomeration and clustering of business types and perceptions of women’s work.
A dissertation submitted to the Faculty of Engineering and the Built Environment in fulfilment of the requirements for the degree of Master of Science in Urban and Regional Planning by Research
Keywords: Women-owned business enterprises; Businesswomen--South Africa; Entrepreneurship